Pengaruh Personal Selling dan Sales Promotion terhadap Keputusan Pembelian Jasa Event Organizer di Bepro Communication - Kusumaningrum, Prabawati Nugroho; Wirata, I Nengah; Sumadi, I Gede (Journal of Event and Convention Management, 2024)
Bali Island as a tourism destination continues to grow every year, especially in the MICE and event industry. The intense competition in this industry has forced event organizers to carry out various promotional strategies. This research aims to analyze the effect of personal selling and sales promotion in an effort to increase sales volume for event organizer services. This research uses a quantitative descriptive approach. Data was collected through a questionnaire instrument which was distributed to 80 project managers from each company that used services in holding events from 2018 to 2022. Data were processed using SPSS version 26 and analyzed using multiple linear regression, classical assumption regression test, individual parameter significance test (t test), simultaneous significance test (F test) and the coefficient of determination R². Based on the results of data analysis it is known that personal selling and sales promotion have a positive and significant effect on purchasing decisions for event organizer services either partially or simultaneously. Simultaneously it is 70.5%, while the remaining 29.5% is influenced by other factors not examined. Partially, personal selling has a positive and significant effect of 23.4% on purchasing decisions, while sales promotion has a positive and significant effect of 28.2% on purchasing decisions.